Language and Systems Theory: Critical Remarks on the Luhmannian Conception - Calise, Santiago Gabriel (2020)
Language and Systems Theory: Critical Remarks on the Luhmannian Conception. This paper assesses Luhmann’s conception of language as structural coupling. Luhmann treated language as a medium, but also tried to incorporate the Saussurean concept of sign. The paper will deal with three conflictive points. The first one is the erasure of all psychic refer-ence that Luhmann performs. The second issue is Luhmann’s refusal to consider language as a system. The third point poses the question about the ontological bases of language, in comparison to those of the autopoietic systems.